Cross-modal correspondences : sensory processing differences between psychology and art, design & media undergraduates - Huang, Amanda Faith Kim Li (2017)
Human beings display a strong tendency to pair certain visual and auditory attributes together. In particular, the words bouba/maluma and takete/kiki are consistently mapped to rounded and spiky objects respectively across different age groups, cultures and in a seemingly unconscious fashion. A distinct field of research on sensory integration has also explored how human beings consciously regulate sensory information across and within different modalities to match their preferences. A third stream of evidence has also underlined that more creative individuals (eg. artists) possess stronger sensory connectivity. Thus, this study sought to investigate if a relationship between the fields of Sound Symbolism and Sensory Integration exists, and if so, whether more creative individuals would display a stronger tendency to make these prevailing shape-sound mappings. Participants were 135 undergraduates from Nanyang Technological University. Undergraduates pursuing Art, Design and Media (ADM) were hypothesised to have different sensory integration abilities (as measured by the Sensory Profile) than their Psychology counterparts. ADM undergraduates were also hypothesised to make more congruent mappings between shape-sound stimuli, as measured by the Alien Zoo task. By comparing whether one’s Major generated differences in task performance and whether individual differences in sensory integration were linked to differences in cross-modal processing, the expected relationship was not observed. However, an unexpected finding of the study was that undergraduates of both majors did not perform “Similar to Most People” on the Sensory Profile tool – a finding that has important implications for the future clinical use of the tool in Singapore.